ESTIMATION OF TOTAL PHENOLIC AND FLAVONOIDS CONTENT FROM EXTRACT OF WRIGHTIA TINCTORIA (ROXB) R. BR. LEAVES AND EVALUATION OF ITS ANTIOXIDANT ACTIVITY - T. SENTHIL KUMAR,; D. VENKAPPAYYA,; VILAMBI N.R.K. REDDY,; R. MANAVALAN, (International Journal of Pharma and Bio Sciences, 2014)
Flavonoids are widely distributed in Plant Kingdom that act as free radical scavengers and play a vital role in combating various diseases through their antioxidant property. An attempt was made to evaluate the antioxidant property of free and bound flavonoids present in Wrightia tinctoria (Roxb) R.Br. leaves (Apocynaceae). An initial estimation of total phenolic and flavonoid content after methanolic extraction of powdered leaves of Wrightia tinctoria (Roxb) R.Br. was done. Total phenolic content of 30.17 ± 2.36 mg/g (gallic acid equivalents /g of dry extract) and total flavonoid content of 21.33 ± 0.94 mg/g (quercetin equivalents /g dry extract) was obtained when estimated through Folin Ciocalteu reagent method and aluminum chloride colorimetric method respectively. The total antioxidant activity (by determination of phosphomolybdenum reduction) was found to be maximum [86.56 ± 2.20 mg/g (ascorbic acid equivalents /g of dry extract)] for free flavonoid fraction obtained from the methanolic extract when compared to the bound flavonoid extract (43.88 ± 2.56 mg/g). This result indicates that the polyphenols present in free flavonoid extract may be responsible for the enhanced activity. Wrightia tinctoria (Roxb) R.Br. is used for the treatment of skin infections since time immemorial and this finding on its antioxidant property documents a possible contributing mechanism by which it heals skin infections and provides an evidence for presence of polyphenols and free flavonoids in large quantity in its leaves.